SUBTRACTIVE GENOMICS APPROCH TO IDENTIFY POTENTIAL THERAPEUTIC TARGETS IN LEISHMANIA DONOVANI - RAJENDRA HARIBHAU MANDAGE; AMOL SHRIRAM WADNERKAR (International Journal of Pharma and Bio Sciences, 2010)
Availability of gene and protein sequences of parasite has provided a remarkable amount of data that can be useful in drug target identification and vaccine development. Although extensive researches are on way in order to control the disease caused by eukaryotic parasites and to develop drug(s) against them, till date no effective vaccine or specific drug is available. Subtractive genomics approach is one of the recently adopted methodology in which the subtraction of sequence between the host and parasite proteome provides information for a set of proteins that are likely to be essential to the parasite but absent in the host. We have used the same methodology to analyse the proteome of the human parasite Leishmania donovani .Our analysis showed that out of the 446 protein sequences of the parasite, 29 represent unique to parasite and predicted as putative drug targets. 16 membrane, 5 nuclear, 3 cytoplasmic along with 2 mitochondrial are found to be the potential drug targets by using subtractive genomics approach. The preliminary work presented here identifies a small subset of the L. donovani proteome that might be investigated further for identifying potential drug and vaccine candidate in this parasite.